The work ethics of Malay construction project managers / Madinah Hussin Torrance - Torrance, Madinah Hussin (2007)
The general objective of this study was to understand the nature of the work ethics of Malay construction project managers. In particular the research sought to determine a) their work values, b) how they perceive their job, c) how committed are they to their work and how ethical are they. The study was divided into three phases. In phase 1, a questionnaire survey was conducted to reveal their work values. In phase 2, participants selected from among the respondents in Phase 1 were interviewed using a modified Repertory Grid method to determine how they perceived their work. In addition, participants' commitment to their work and their ethical standards were gathered using Vignettes. In Phase 3, the results were validated through a questionnaire survey of feedback from participants' colleagues, superiors and subordinates. From the results of Phases 1, 2 and 3 it was identified that Malay construction project managers had strong Islamic values, clear work ethics and positively identified with their profession. Participants showed strong willingness to work but were not willing to extend work far into their family time. A large majority believed that they should exert moderate control on their subordinates because subordinates were believed to be team members. Trust was preferred. In conforming to Islamic values, they were against cheating, cutting corners, ignoring safety procedures and transgressing project managers' professional code of conduct. However, the culture of giving gifts and business entertainments were generally believed to be acceptable as a gesture of good relationships. A large majority of the participants perceived their job positively with a high of 85% of the participants declaring that if they were to relive their lives, they would choose to be project managers. In the comparison of their profession with other professions, participants saw the Doctors as much higher. Religious teachers were valued but they were seen as idealists, whereas as construction project mangers they had to be realists. Participants saw their work as having many similarities to the Chefs and to some extent the Actors. However, the lawyers were somewhat negatively perceived.